1994
DOI: 10.1021/jm00031a020
|View full text |Cite
|
Sign up to set email alerts
|

An X-ray Crystallographic Study of the Nonsteroidal Contraceptive Agent Centchroman

Abstract: We have determined an X-ray crystal structure for the N-methyl iodide derivative of the nonsteroidal contraceptive centchroman. The pendant aromatic substituents on C-3 and C-4 of the chroman system are nearly perpendicular to the plane of the chroman system, an orientation expected in such a chroman, but perturbed to some degree by the gem dimethyl substituents at C-2. Structural superposition with other nonsteroidal antiestrogens, tamoxifen and nafoxidine, shows a similar disposition of the tertiary amine si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Many reports have found that the ligand binding to nuclear hormone receptors such as PPARα, PPARβ, PPARγ, retinoid acid receptor (RAR) and oestrogen receptor (ER) increased DNA‐binding, dimerization and transcriptional activities (Jans, 1994; MacLean et al ., 1997; Clevenger, 2003; Claessens and Gewirth, 2004; Smith and O'Malley, 2004). For example, binding of a selective oestrogen modulator, tamoxifen, to ERs induced conformational alterations, thus affecting the ability of ERs to interact with other proteins, such as co‐activators and co‐repressors and to modulate target gene transcription (Kuroda et al ., 1985; Ray et al ., 1994; Brzozowski et al ., 1997; Shiau et al ., 1998). Likewise, TM‐25659 may directly bind to TAZ and promote conformational changes and subsequent interaction with various transcription factors such as RUNX2 and PPARγ.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have found that the ligand binding to nuclear hormone receptors such as PPARα, PPARβ, PPARγ, retinoid acid receptor (RAR) and oestrogen receptor (ER) increased DNA‐binding, dimerization and transcriptional activities (Jans, 1994; MacLean et al ., 1997; Clevenger, 2003; Claessens and Gewirth, 2004; Smith and O'Malley, 2004). For example, binding of a selective oestrogen modulator, tamoxifen, to ERs induced conformational alterations, thus affecting the ability of ERs to interact with other proteins, such as co‐activators and co‐repressors and to modulate target gene transcription (Kuroda et al ., 1985; Ray et al ., 1994; Brzozowski et al ., 1997; Shiau et al ., 1998). Likewise, TM‐25659 may directly bind to TAZ and promote conformational changes and subsequent interaction with various transcription factors such as RUNX2 and PPARγ.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, administration of 1.25 mg/kg per day dose of ormeloxifene over a longer period as would be required in clinical condition or titration of its dose/schedule might provide the regimen for optimal protection against post-menopausal bone loss, without significantly stimulating endometrial/breast tissue. Levormeloxifene, the l-analog of this molecule, which is a more potent receptor binder with relative binding affinity (RBA: 15.7 ± 3.1% of estradiol-17␤) to rat uterine cytosol estrogen receptors (ER) [25], has recently been reported to inhibit bone loss in estrogen-deficient animal models [26]. In a double blind clinical trial, decrease in serum total alkaline phosphatase and urine excretion of C-terminal extension peptides has also been observed in post-menopausal women treated for 35 (20,80 or 160 mg) or 56 (40 or 80 mg) days, indicating its estrogen-like bone preserving effect, but caused endometrial thickening due to fluid retention, without evidence of proliferation or hyperplasia [24].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the search for related but different agents has intensified considerably over the last few years. [4][5][6][7][8] Recently, it was discovered that grafting a ferrocenyl unit onto the tamoxifen skeleton allowed the preparation of a new and promising class of ferrocifen-type breast-cancer drug candidates. [9][10][11][12] These new molecules, called "hydroxyferrocifens" by analogy to tamoxifen, present the advantage of exhibiting dual functionality.…”
Section: Introductionmentioning
confidence: 99%
“…However, tamoxifen is active only against tumors that are estrogen‐receptor positive (ER+), and frequently gives rise to resistance after prolonged use. As a consequence, the search for related but different agents has intensified considerably over the last few years 48. Recently, it was discovered that grafting a ferrocenyl unit onto the tamoxifen skeleton allowed the preparation of a new and promising class of ferrocifen‐type breast‐cancer drug candidates 912.…”
Section: Introductionmentioning
confidence: 99%